2018
DOI: 10.1002/cbic.201800400
|View full text |Cite
|
Sign up to set email alerts
|

Genomics‐Driven Discovery of a Symbiont‐Specific Cyclopeptide from Bacteria Residing in the Rice Seedling Blight Fungus

Abstract: The rice seedling blight fungus Rhizopus microsporus harbors endosymbiotic bacteria (Burkholderia rhizoxinica) that produce the virulence factor rhizoxin and control host development. Genome mining indicated a massive inventory of cryptic nonribosomal peptide synthetase (NRPS) genes, which have not yet been linked to any natural products. The discovery and full characterization of a novel cyclopeptide from endofungal bacteria is reported. In silico analysis of an orphan, symbiont-specific NRPS predicted the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…5c, Supplementary Fig. 35) 46 . All frs C starter domains form a deeply rooted clade, supporting their close relationship and highlighting differences to the other domains in the database, even from the same taxa.…”
Section: Characterization Of a Cultivable Fr Producermentioning
confidence: 99%
“…5c, Supplementary Fig. 35) 46 . All frs C starter domains form a deeply rooted clade, supporting their close relationship and highlighting differences to the other domains in the database, even from the same taxa.…”
Section: Characterization Of a Cultivable Fr Producermentioning
confidence: 99%
“…5). For example, by a combination of genome mining and chemical analytics, a number of nonribosomally synthesized peptides were identified from the endosymbiont of the plant-pathogenic fungus Rhizopus microsporus that are involved in the bacterial-fungal interaction and/or serve an ecological function [117][118][119] . The endofungal bacteria also produce cytotoxic necroximes (e.g., necroxime A, 33) in symbiosis with the fungal host.…”
Section: Genome-guided Discovery Of Natural Products From Ecological Interactionsmentioning
confidence: 99%
“…Investigations on the mucoromycete Rhizopus microsporus revealed that its D-amino acid-containing peptides rhizonin and heptarhizin are not produced by the fungus but by its in-host endosymbiotic proteobacterium Paraburkholderia rhizoxinica (31,32). Similarly, Burkholderia-related (BRE) endosymbionts such as Mycoavidus cysteinexigens are frequently observed in Mortierellales (33,34).…”
Section: Introductionmentioning
confidence: 99%